Claims for stacking and handing of anti-seismic steel bar of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding claims for stacking and handing of anti-seismic steel bar of BRAC University new campus project.